PENGEMBANGAN MEDIA PEMBELAJARAN KONSEP LUAS BIDANG DATAR BERBASIS PERANGKAT LUNAK GEOGEBRA - Sandi Ramdhani (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2017)
Abstract This study aims to produce GeoGebra-based learning media of plane area concept that is valid, practical, and has good potential effects. This research use development research method or development research of formative research type which is simplified. Learning media development procedure in this research consists of 3 stages: 1) self evaluation, 2) prototyping (validation, evaluation and revision), 3) Field test. The results of research can be explained that: 1) the development of GeoGebra-based learning media of plane area concept in MTs Kab. Bandung valid based on contents, language, and conformity of context used and practical based on ease of use of students, 2) trials result of development of GeoGebra-based learning media of plane area concept given in MTs Kab. Bandung has a potential effect, namely: students love to learn with computer media, students love to learn with GeoGebra software, GeoGebra-based learning media of plane area concept helps students understand the area concept, learning media of area rectangular is most helpful to students understand the area concept.Keywords: learning media, GeoGebra, area, plane